English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-10-23 10:24:36 · 12 answers · asked by ;) 3 in Science & Mathematics Mathematics

12 answers

3y(2y-7) + 2(y-5)
6y² - 21y + 2y -10
6y² -19y -10

Hope this helps!

2007-10-23 10:29:27 · answer #1 · answered by Anonymous · 2 3

there's a trick to the question . forget approximately regarding the squared (x+2y-5)^2 + (2x+y-7)^2 = 0 x+2y-5 = 0 2x+y-7 = 0 x + 2y = 5 (a million) 2x + y = 7 (2) you could now sparkling up via substitution . x = 5 -2y Sub that into equation 2 2(5 -2y ) + y = 7 10 -4y + y =7 -3y = -3 y = a million Sub that into equation1 x + 2(a million) = 5 x = 3 this is all in case you plug that for the duration of you're able to get the equation to be 0. i think of that there is basically one unique answer because of the fact the above equation is an ellipse.

2016-10-04 10:59:49 · answer #2 · answered by Anonymous · 0 0

i can assure you that this is the correct answer:

6y^2-21y+2y-10
6y^2-19y-10
(2y-5) (3y+2)
therefore: solve for x: 2y-5=0 therefore y=5/2
3y+2=0 therefore y=-2/3

the boy above me has put 2/3 . this should be - 2/3

you have 2 solutions for x - i know this is correct, trust me!!

2007-10-23 10:41:40 · answer #3 · answered by heaven - 7 1 · 1 0

factored its this: (3y-2)(2y-5) from 6y^2-19y-5
3y-2=0 & 2y-5=0
3y=2 2y=5
y=2/3 y= 5/2
this is a complete answer.

2007-10-23 10:37:07 · answer #4 · answered by Daniel P 6 · 0 0

6 y ² - 19 y - 10

2007-10-24 06:23:03 · answer #5 · answered by Como 7 · 0 0

3y(2y-7) + 2(y-5)
6y^2 - 21y + 2y - 10
6y^2 - 19y - 10

If you want it completely factored im too lazy to use the quad. formula.

2007-10-23 10:32:34 · answer #6 · answered by aaron.brake 3 · 1 2

6y squared minus 21y plus 2y minus 10

Which equals to 6y squared-19y-10, I think. Double check my work.

2007-10-23 10:35:07 · answer #7 · answered by C F 2 · 0 1

3y^2 - 21y + 27 - 10 =
3y^2 - 21y +17

2007-10-23 10:34:35 · answer #8 · answered by Brian V 1 · 0 2

6y^2 - 21y + 2y - 10 = 6y^2 - 19y -10

2007-10-23 10:30:44 · answer #9 · answered by tj is cool 5 · 1 2

~The Correct answer is ~
6y^2 - 21y + 2y - 10 = 6y^2 - 19y -10

Now give me a harder question!!!

2007-10-23 10:34:07 · answer #10 · answered by Anonymous · 0 2

fedest.com, questions and answers